Strategic Human Resource Management at GlocalFarm Ltd. - Oluwasanmi, Oluwaseun; Adewale Adeyemi, Adewale; Akinbola, Femi (IIUM Journal of Case Studies in Management, 2025)
This case exemplifies the role of Human Resource Management (HRM) in the agricultural sector, emphasising its strategic practices, impacts on employee performance, and contributions to organizational success. It shows how HRM facilitates organisational change, addresses key challenges unique to agriculture, and offers practical solutions in GlocalFarm Ltd. Thematic include recruitment strategies, training and development, health and safety measures, and the integration of technology. The case highlights how effective HRM practices not only enhance productivity and employee satisfaction but also foster adaptability in the face of agricultural industry changes, ultimately pushing for long-term growth and sustainability in agricultural firms.